Dangerous and severe: process, programme, and person; Grendon's work - Morris, Mark (Community, culture and change, 2004)
Grendon prison : an introduction -- Grendon's men -- Grendon's process -- Grendon's programme : models of change -- Grendon staff : clinical pluralism -- Grendon as a psychodynamic treatment -- Dilemmas in management -- Evidence and audit -- Looking forwards and DSPD.